2013
DOI: 10.1159/000350229
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of the Effect of Mouth Rinse with Trimetaphosphate on Enamel Demineralization

Abstract: Objective: The aim of this study was to investigate the effectiveness of sodium trimetaphosphate (TMP) addition to mouth rinses to inhibit enamel demineralization. Design: Bovine enamel blocks (n = 88) were selected by surface hardness and divided into eight treatment groups (n = 11 per group): placebo, 100 or 225 μg F/ml; the rinses with 100 μg F/ml had differing TMP concentrations (range 0-0.6%). The blocks were subjected to pH cycling for 5 days and treated twice a day with mouth rinses. After that, surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…Thus, the data obtained using this model (or any other in vitro protocol) should be considered carefully. This statement is supported by data from this study that observed reduction in F concentration in the hydroxyapatite with the addition of TMP, while in the study by Favretto et al (8) there was an increase of F in the enamel with 0.4% TMP. The adsorption of TMP on enamel surface can modify the selective permeability of the enamel by facilitating the diffusion of ions (12,14,20).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Thus, the data obtained using this model (or any other in vitro protocol) should be considered carefully. This statement is supported by data from this study that observed reduction in F concentration in the hydroxyapatite with the addition of TMP, while in the study by Favretto et al (8) there was an increase of F in the enamel with 0.4% TMP. The adsorption of TMP on enamel surface can modify the selective permeability of the enamel by facilitating the diffusion of ions (12,14,20).…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have suggested that TMP reduces the demineralization process, and that an ideal TMP/F ratio allows an enhancement of the effects of F-containing products (7,8,(10)(11)(12)(13). When TMP and F are co-administered, the adsorption of TMP on the enamel surface can change the selective permeability and facilitate the diffusion of ions such as Ca and F (12) into the enamel (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations